Analisis Status Keberlanjutan Perkebunan Kelapa Sawit Rakyat Provinsi Jambi - Ida Kurnia Saragih; Dwi Rachmina; Bayu Krisnamurthi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
Oil palm plantations are strategic commodities in the national economy and public welfare. Smallholder oil palm plantations as part of the palm oil commodity supply chain currently face business sustainability issues. This study aims to analyze the sustainability of community oil palm plantations based on index assessment using the Rap-Palmoil method through the Multidimensional Scaling (MDS) method. Multidimensional analysis of MDS in terms of economic, social, environmental, institutional, and technological dimensions as aspects examined in this study. This research was conducted in two regencies of oil palm plantations in a broad area of ​​land in Jambi Province, namely Muaro Jambi Regency and Merangin Regency. The data used are primary and secondary data, primary data are obtained from interviews with farmers while secondary data are obtained from the Central Statistics Agency, Plantation Service, and literature that supports this research. Respondents in this study were 99 farmers selected purposively. The results of the multidimensional sustainability analysis of the Jambi Province oil palm plantation sustainability index were 57,79 included in the quite sustainable category. While the results of the sustainability index analysis for the five dimensions are 54,11 (economy), 66,83 (social), 58,64 (environmental), 46,40 (institutional), 59,02 (technology). All dimensions are overall included in the